2014
DOI: 10.1038/cdd.2014.83
|View full text |Cite
|
Sign up to set email alerts
|

Death receptor-independent FADD signalling triggers hepatitis and hepatocellular carcinoma in mice with liver parenchymal cell-specific NEMO knockout

Abstract: Hepatocellular carcinoma (HCC) usually develops in the context of chronic hepatitis triggered by viruses or toxic substances causing hepatocyte death, inflammation and compensatory proliferation of liver cells. Death receptors of the TNFR superfamily regulate cell death and inflammation and are implicated in liver disease and cancer. Liver parenchymal cell-specific ablation of NEMO/IKKc, a subunit of the IjB kinase (IKK) complex that is essential for the activation of canonical NF-jB signalling, sensitized hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 37 publications
4
47
0
Order By: Relevance
“…37,39 Consistently, an independent study showed that LPC-specific knockout of caspase-8 also protected NEMO LPC-KO mice from hepatocyte apoptosis and the development of liver cancer. 37,39 Consistently, an independent study showed that LPC-specific knockout of caspase-8 also protected NEMO LPC-KO mice from hepatocyte apoptosis and the development of liver cancer.…”
Section: The Interplay Between Ikk/nf-κb and Ripk1 In Liver Homeostmentioning
confidence: 80%
See 1 more Smart Citation
“…37,39 Consistently, an independent study showed that LPC-specific knockout of caspase-8 also protected NEMO LPC-KO mice from hepatocyte apoptosis and the development of liver cancer. 37,39 Consistently, an independent study showed that LPC-specific knockout of caspase-8 also protected NEMO LPC-KO mice from hepatocyte apoptosis and the development of liver cancer.…”
Section: The Interplay Between Ikk/nf-κb and Ripk1 In Liver Homeostmentioning
confidence: 80%
“…37,39 Consistently, an independent study showed that LPC-specific knockout of caspase-8 also protected NEMO LPC-KO mice from hepatocyte apoptosis and the development of liver cancer. 39 In light of an earlier study reporting that systemic TNFR1 deficiency largely ameliorated liver damage and tumorigenesis, 41 we also generated and analyzed NEMO LPC-KO Tnfr1 −/− mice but found that systemic lack of TNFR1 did not prevent liver damage and only had a mild effect in slowing down tumor progression. Surprisingly NEMO LPC-KO mice with hepatocyte-specific deficiency of TNFR1, Fas or TRAILR, individually or combined, were not protected from the liver pathology, suggesting that these death receptors are not essential drivers of hepatocyte apoptosis in this model.…”
Section: The Interplay Between Ikk/nf-κb and Ripk1 In Liver Homeostmentioning
confidence: 80%
“…44, 51, 52 Surprisingly, apoptosis is strongly prevented by crossing NEMO LPC-KO mice with RIPK1 kinase dead mice while poorly with Ripk1 LPC-KO . 44 As NEMO LPC-KO mice presented elevated TNF- α in the liver compared with WT mice, 51 additional RIPK1 deficiency could induce hepatocyte apoptosis in a TNF- α -dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB signaling regulates immune and inflammatory responses and cell survival (12,13) and is implicated in the pathogenesis of hepatitis and HCC (14,15). Mice with liver parenchymal cell-specific (LPC-specific) ablation of NF-κB essential modulator (NEMO)/IκB kinase γ (IKKγ), the regulatory subunit of the IKK complex that is required for canonical NF-κB activation, developed spontaneously chronic hepatitis and HCC due to RIPK1 kinase activity-driven, FAS-associated death domain (FADD)/ caspase-8-mediated hepatocyte apoptosis (16)(17)(18)(19). In contrast, LPC-specific NF-κB deficiency did not cause spontaneous development of severe chronic liver disease and cancer, suggesting that NEMO regulates liver homeostasis by NF-κB-dependent and -independent functions (16).…”
Section: Introductionmentioning
confidence: 99%